Дијагностичка вредност серума Ahd-5, IL1RL1 и CD138 код пацијената са хроничном срчаном инсуфицијенцијом: Серум Ахд-5, ИЛ1РЛ1 и ЦД138 код КХД-а - Ruan, Wenqiang; Wang, Jiajia; Li, Lingyun; Jia, Yuanchao (Journal of Medical Biochemistry, 2026)
Objective To explore the diagnostic value of serum Aldehyde dehydrogenase 5 (Ahd-5), IL-1 receptor-like 1 (IL1RL1), and CD138 in patients with chronic heart failure (CHF).Methods The study group consisted of 256 CHF patients who were treated at our hospital between February 2023 and March 2025, whereas the control group consisted of 138 healthy volunteers who came to our hospital during that period for physical examinations. The cardiovascular function markers (LVEF, LVESV and LVEEDV) as well as the serum markers (Ahd-5, IL1RL1, CD138, and N-terminal pro-B-type natriuretic peptide, or NT-proBNP), were identified and compared. According to the LVEF results, the CHF patients were divided into the reduced ejection fraction heart failure (HFrEF) group, the mildly reduced ejection fraction heart failure (HFmrEF) group, and the preserved ejection fraction heart failure (HFpEF) group. Serum Ahd-5, IL1RL1, and CD138 levels of CHF patients were correlated with cardiac function markers using Pearson correlation analysis. The associations among the various severities of CHF patients and their serum Ahd-5, IL1RL1, and CD138 levels were examined using Spearman correlation analysis. The factors impacting the occurrence of CHF were examined. The diagnostic value of serum Ahd-5, IL1RL1, and CD138 levels for CHF patients was examined using a receiver operating characteristic (ROC) curve.Results Compared to the control group, the study group's serum levels of Ahd-5 and LVEF were significantly lower (P
Keywords: Хронична срчана инсуфицијенција; Алдехид дехидрогеназа 5; ИЛ-1 рецептор сличан 1; ЦД 138; Дијагностичка вредност